2017
DOI: 10.1136/bmjopen-2017-016403
|View full text |Cite
|
Sign up to set email alerts
|

Association between preoperative anaemia with length of hospital stay among patients undergoing primary total knee arthroplasty in Singapore: a single-centre retrospective study

Abstract: ObjectivesStudies in western healthcare settings suggest that preoperative anaemia is associated with poor outcomes after elective orthopaedic surgery. We investigated the prevalence of preoperative anaemia among patients with primary unilateral total knee arthroplasty (TKA) in Singapore and its association with length of hospital stay (LOS), perioperative blood transfusion and hospital readmission rates.MethodsRetrospective cohort study performed in a tertiary academic medical centre in Singapore, involving p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
79
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 43 publications
11
79
0
1
Order By: Relevance
“…A recent observational study found pre‐operative anaemia — defined as haemoglobin concentration < 130 g/L — in 32% of patients undergoing elective TKA, and, based on the results for the orthopaedic surgical cohort from this study, it is likely that most of these patients were iron depleted . A 2017 single‐centre retrospective study similarly reported anaemia in 24% of a similar cohort of patients, and found it was associated with an increased risk of hospital stay in excess of 6 days (unadjusted odds ratio [OR], 1.97; 95% confidence interval [CI], 1.53–2.53; P < 0.001), which escalated further and proportionally with decreasing haemoglobin cconcentration . In another observational study, anaemia was associated with an increased risk of post‐operative complications in aseptic revision joint arthroplasty (OR, 1.45; 95% CI, 1.24–1.70; P < 0.001), mortality (OR, 2.18; 95% CI, 1.09–4.36; P = 0.028), and increased hospital length of stay (adjusted coefficient, 1.02 days; 95% CI, 0.73–1.31; P < 0.001) …”
mentioning
confidence: 64%
“…A recent observational study found pre‐operative anaemia — defined as haemoglobin concentration < 130 g/L — in 32% of patients undergoing elective TKA, and, based on the results for the orthopaedic surgical cohort from this study, it is likely that most of these patients were iron depleted . A 2017 single‐centre retrospective study similarly reported anaemia in 24% of a similar cohort of patients, and found it was associated with an increased risk of hospital stay in excess of 6 days (unadjusted odds ratio [OR], 1.97; 95% confidence interval [CI], 1.53–2.53; P < 0.001), which escalated further and proportionally with decreasing haemoglobin cconcentration . In another observational study, anaemia was associated with an increased risk of post‐operative complications in aseptic revision joint arthroplasty (OR, 1.45; 95% CI, 1.24–1.70; P < 0.001), mortality (OR, 2.18; 95% CI, 1.09–4.36; P = 0.028), and increased hospital length of stay (adjusted coefficient, 1.02 days; 95% CI, 0.73–1.31; P < 0.001) …”
mentioning
confidence: 64%
“…Seung-Chan Kim et al [12] found a lower incidence of postoperative prosthetic-related complications in the simultaneous THA group. When it turns to TKA, several studies reported a lower rate of complications in the simultaneous TKA group [14,16,19,24,25]. Whereas some studies have reported a higher rate of speci c complications, such as venous thromboembolism (VTE) [7] and myocardial infarction (MI) [26] for the patients older than 65 years in the simultaneous TKA group.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged LOS will not only have a negative impact on health outcomes, causing iatrogenic illness easily, but also high hospital occupancy resulted in a resultant loss of efficiency and access, all of which would bring a marked increase in health expenses [21,22]. And this might be explained the relationship between exceeding LOS with high cost, for long LOS unusually followed high costs [21][22][23].…”
Section: Discussionmentioning
confidence: 99%